Federal Rules of Evidence - Cornell Law School. Legal Information Institute, author (Open Textbook Library, 2015)
These rules govern the introduction of evidence in proceedings, both civil and criminal, in Federal courts.
Article 1: General Provisions -- Article 2: Judicial Notice -- Article 3: Presumptions in Civil Cases -- Article 4: Relevance and Its Limits -- Article 5: Privileges -- Article 6: Witnesses -- Article 7: Opinions and Expert Testimony -- Article 8: Hearsay -- Article 9: Authentication and Identification -- Article 10: Contents of Writings, Recordings, and Photographs -- Article 11: Miscellaneous Rules
These rules govern the introduction of evidence in proceedings, both civil and criminal, in Federal courts. While they do not apply to suits in state courts, the rules of many states have been closely modeled on these provisions. Our Federal Rules ebooks include: The complete rules as of December 1, 2012 (for the 2013 edition). All notes of the Advisory Committee following each rule. Internal links to rules referenced within the rules. External links to the LII website's version of the US Code.
Keywords: law